Body connection mediates the relationship between traumatic childhood experiences and impaired emotion regulation in borderline personality disorder - Schmitz, Marius; Bertsch, Katja; Löffler, Annette; Steinmann, Sylvia; Herpertz, Sabine; Bekrater-Bodmann, Robin (Borderline Personality Disorder and Emotion Dysregulation, 2021)
Previous studies revealed an association between traumatic childhood experiences and emotional dysregulation in patients with borderline personality disorder (BPD). However, possible mediating pathways are still not fully understood. The aim of the present study was to investigate the potential mediating role of body connection, describing the awareness of the relationship of bodily and mental states, for the association between a history of traumatic childhood experiences and BPD core symptomatology.